Le moustique, ennemi public n° 1 ? - Lecollinet, Sylvie (éditions Quae, 2022)
The invasive presence of mosquitoes and their pathogens is changing our daily lives and challenging our lifestyles. Mosquitoes contribute to thousands of deaths worldwide each year by transmitting various parasites and viruses, responsible for diseases with well-known names: malaria, dengue, zika, chikungunya, etc. What is less well known, however, is that mosquitoes also contribute to the balance of ecosystems as a source of food for many species and help pollinate plants. Their great morphological, biological, ecological and genetic diversity must be well understood before solutions can be considered to better control their spread and outbreak, and thus control the transmission of pathogens. Faced with this rapidly evolving threat, innovative and concerted strategies to control these insects are being deployed in many countries. Aimed at a wide audience, but also at students and their teachers, this book, illustrated with numerous examples, is a synthesis of knowledge on mosquitoes and current control methods.